Image-based haptic roughness estimation and rendering for haptic palpation from in vivo skin image. - Kim, Kwangtaek (Medical & Biological Engineering & Computing, 2018)
Despite the advancement of measuring technologies, there was a need for palpation by hands to be able to better diagnose skin diseases and to learn about the tactile properties of in vivo skin surface. However, directly touching in vivo skin surface can cause secondary infections or damages. Therefore, a technology providing infection- and damage-free skin palpations and precise haptic skin roughness rendering is needed. A multidimensional (2D and 3D) rendering system was developed for multimodal (visual and haptic) rendering that can run with any given in vivo input skin images. For haptic rendering, a commercial haptic device with 3 degrees of freedom (3DOF), Geomagic Touch X, was used. To improve haptic roughness rendering, a force shading algorithm that reduces force discontinuity on rough surface patches but preserves the original roughness values was implemented and applied. In addition, a new image-based roughness estimation method was introduced and the results were compared with haptic roughness results to verify roughness rendering in the system. The developed haptic roughness rendering system will help to diagnose abnormalities on in vivo skin surfaces by virtual haptic palpation with no concern about secondary infections or damages (caused by touch interactions) especially in case of psoriasis, atopic dermatitis, or aging, which results in significant changes of skin roughness. Besides, the system can also be a good tool to examine skin condition changes before and after the use of skin care products (cosmetics). In addition, the proposed 2D skin roughness estimation method can be applied for mobile applications to provide an online roughness estimation tool with a simple phone camera.